Penguatan Kapasitas Kelompok Sadar Wisata (Pokdarwis) dalam Mengembangkan Ekowisata Berkelanjutan di Kepulauan Kabupaten Mempawah - Jumardi Budiman; Okianna, Okianna; Minsas, Sukal; Kuncoro, Iwan (Jurnal Pengabdian Kepada Masyarakat, 2025)
Mempawah Regency has abundant marine tourism potential, especially on Datuk, Setinjan, and Temajo Islands, which can be a driver of economic growth for the local community. However, the utilization of this potential is still constrained by the limited managerial capacity of the Jejak Nusa Tourism Awareness Group (Pokdarwis), the lack of supporting facilities, and the weak marketing strategy. The Partnership Community Service (PKM) Activity, funded by the Directorate of Research and Community Service, Directorate General of Research and Development, Ministry of Higher Education, Science, and Technology, aims to strengthen the capacity of Pokdarwis through training, mentoring, and the application of technology and innovation to realize sustainable ecotourism. The implementation method is carried out in a participatory manner through five stages, namely socialization, training, technology application, mentoring and evaluation, and program sustainability planning. Steps include preparing organizational work programs, providing business and financial management training, offering digital marketing assistance through blogs and social media, offering snorkeling facilities and underwater cameras, and facilitating cooperation with the village government and ship owners. The results of the activity showed a significant increase in the aspects of organizational management, finance, and digital marketing of Pokdarwis. Additionally, the presence of new tourism facilities encourages the growth of tourist interest, increases the community's income potential, and fosters social solidarity and environmental awareness. Thus, this program has succeeded in creating an ecotourism-based community empowerment model that supports economic welfare while maintaining the sustainability of marine ecosystems.